How do you find the first and second derivative of y=1/(1+e^-x)?

1 Answer
Jan 9, 2017

dy/dx=(e^(-x))/(1+e^(-x))^2,(d^2y)/(dx^2)=(e^(-2x)-e^(-x))/(1+e^(-x))^3

Explanation:

color(orange)"Reminder " color(red)(bar(ul(|color(white)(2/2)color(black)(d/dx(e^(-x))=-e^(-x))color(white)(2/2)|)))

There are 2 approaches to differentiating this function.

(1)" Using the quotient rule"

(2)" expressing " y=(1+e^(-x))^-1" and use chain rule"

I'll use approach (1) you could perhaps try approach (2). The result will be the same.

differentiate using the color(blue)"quotient rule"

" Given " y=(g(x))/(h(x))" then"

color(red)(bar(ul(|color(white)(2/2)color(black)(dy/dx=(h(x)g'(x)-g(x)h'(x))/(h(x))^2)color(white)(2/2)|)))

g(x)=1rArrg'(x)=0

h(x)=1+e^(-x)rArrh'(x)=-e^(-x)
color(blue)"------------------------------------------------------------"

rArrdy/dx=((1+e^-x).0-1.(-e^-x))/(1+e^-x)^2=(e^-x)/(1+e^-x)^2

" To find " (d^2y)/(dx^2)" differentiate " dy/dx

differentiate using the color(blue)"quotient rule/chain rule"

"here " g(x)=e^-xrArrg'(x)=-e^-x

h(x)=(1+e^-x)^2rArrh'(x)=2(1+e^-x).(-e^-x)rarr

rArrh'(x)=-2e^-x(1+e^-x)
color(blue)"---------------------------------------------------------------"

(d^2y)/(dx^2)=((1+e^-x)^2(-e^-x)-(e^-x).(-2e^-x(1+e^-x)))/(1+e^-x)^4

=(-e^-x(1+e^-x)^2+2e^(-2x)(1+e^-x))/(1+e^-x)^4

=(e^-x(1+e^-x)(2e^-x-1-e^-x))/(1+e^-x)^4larr" factoring"

=(e^-xcancel((1+e^-x))(e^-x-1))/(cancel((1+e^-x)^3

=(e^(-2x)-e^-x)/(1+e^-x)^3